THE ROLES OF CHARACTER EDUCATION IN 21ST CENTURY LEARNING - Endang Komara; Heris Hendriana; Uman Suherman (Kopertis Region IV Jabar and Banten, 2021)
National character development is seen as a collective-systemic effort of a nation-state to bring into reality the life of the nation and state in accordance with its foundations and ideology, constitution, state direction, and its collective potential in the context of civilized national, regional and global life to form a nation that is strong, competitive, with noble character, moral, tolerant, mutual cooperation, patriotic, dynamic, cultured and science-oriented based on Pancasila and imbued with iman and taqwa to Allah The Almighty. The 21st century is known to everyone as the age of knowledge, main foundation for various aspects of life. The 21st century learning paradigm emphasizes the ability of students to think critically, be able to connect knowledge with the real world, master information technology, communicate and collaborate. The achievement of these skills can be achieved by applying appropriate learning methods in terms of materials and skills mastery.